Indonesian Coffee Diplomacy in The Era of Joko Widodo’s Government (2019-2021) - Putra, Rafi Folanda Anggika; Wonoadi, Grace Lestariana (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Indonesia is the 4th (fourth) largest coffee producer after Brazil, Vietnam, and Colombia. In this way, Joko Widodo's government did not stay silent through the Ministry of Foreign Affairs to include a curriculum on coffee for diplomats to encourage the development of the national coffee industry. Indonesian diplomats are also taught to become baristas and deserve to understand Indonesian coffee from its roots before promoting it to outsiders. It is hoped that this paper will be able to answer research questions regarding coffee diplomacy strategies in the era of the Joko Widodo government and improve the Indonesian coffee industry in the international arena through gastrodiplomacy. This study uses a descriptive qualitative method that refers to previous studies and reliable secondary sources. The results of this study describe the Indonesian coffee diplomacy strategy by implementing the six forms of the strategy proposed by Juyan Zhang, namely the product marketing strategy, the food event strategy, the coalition building strategy, the use of opinion leaders’ strategy, the media relations strategy, the education strategy. Indonesia's coffee diplomacy strategy cannot be separated from the contributions of state and non-state actors and strives to build a positive national image for Indonesian coffee. Indonesia merupakan produsen kopi terbesar ke-4 (empat) setelah Brazil, Vietnam, dan Kolombia. Dengan begitu pemerintahan Joko Widodo tak tinggal diam, melalui Kementerian Luar Negeri memasukkan kurikulum tentang kopi bagi diplomat untuk mendorong perkembangan industri kopi nasional. Para diplomat Indonesia juga diajarkan untuk menjadi barista dan layak untuk memahami kopi asal Indonesia hingga akarnya sebelum mempromosikan kepada pihak luar. Diharapkan karya tulis ini mampu menjawab pertanyaan penelitian mengenai strategi diplomasi kopi pada era pemerintahan Joko Widodo dan meningkatkan industri kopi Indonesia di kancah internasional melalui gastrodiplomasi. Penelitian ini menggunakan metode kualitatif deskriptif yang mengacu pada penelitian-penelitian yang telah dilakukan sebelumnya dan sumber sekunder yang dapat dipercaya. Hasil dari penelitian ini memaparkan strategi diplomasi kopi Indonesia dengan menerapkan enam bentuk strategi yang dikemukakan oleh Juyan Zhang yaitu product marketing strategy, food event strategy, coalition building strategy, the use of opinion leaders strategy, media relation strategy, the education strategy. Strategi diplomasi kopi Indonesia tidak lepas dari kontribusi aktor negara dan non-negara serta berusaha untuk membangun citra nasional yang positif untuk kopi Indonesia.